KURANGNYA PEMAHAMAN SISWA PADA MATERI PERKALIAN DI KELAS 5 SDN CIPOCOK JAYA 2 - Siti Fathonah; Devi Maulida Rahmah; Fitriani; Valentina Silalahi; Patra Aghtiar Rakhman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Learning mathematics in elementary school is one of the things that is a very interesting study because there are certainly differences in characteristics, especially between the nature of children and the nature of mathematics. The indicators of mathematical problems are a lack of understanding of the basic concepts of multiplication, difficulty in understanding multiplication problems, and a lack of mastery of procedures or steps in solving multiplication problems. This research aims to understand mathematical concepts, explain the relationship between concepts, and apply concepts, use reasoning on patterns and properties, carry out mathematical manipulations in generalizations, compose mathematical evidence and statements. Solve problems and communicate ideas using symbols, tables, diagrams to explain a situation and have an attitude of respect for the use of mathematics in everyday life. This research uses qualitative methods, data collection techniques used are direct observation, interviews and learning outcomes in the form of Mid-Semester Assessment (PTS) scores for class V students. The results of the research show that class 5 students for the 2023/2024 academic year can still be said to lack understanding of the material. multiplication. Thus, students who experience deficiencies in understanding multiplication material can be influenced by factors that cause low mathematics learning outcomes, namely the application of conventional learning models, such as lectures, questions and answers, and giving assignments. Apart from that, solutions that can be taken to deal with students' lack of understanding of multiplication material are by providing motivation, enthusiasm and guidance to students, innovating the learning media used, using methods and using the Contextual Teaching and Learning (CTL) model which has been proven to be effective in increasing students' mastery of the concept of multiplication and the need for collaboration with parents to participate in guiding and monitoring the students' learning process while at home.